The impact of Airbnb on hidden and sustainable tourism: the case of Italy. (25th September 2019) - Contu, Giulia; Conversano, Claudio; Frigau, Luca; Mola, Francesco
Aim of this paper is to investigate the extent of the impact of the Airbnb phenomenon on tourism indicators in general and, in particular, on sustainable tourism indicators (STI). We conjecture that, notwithstanding the correctness of STIs construction, these indicators measure the tourism impact partially, since STIs are computed using data recorded by official statistics organisation that do not include information about Airbnb flows. We demonstrate that Airbnb data offer a new point of view in the analysis of tourism impact in terms of sustainability. Results provide evidence about the substantial presence of Airbnb guests in Italy and the consequent relevant effect on economic, social and environmental sustainability of Italy as a destination.